Influence of Critical Infrastructure on Enterprise Economic Security - Strelcova, Stanislava; Rehak, David; Johnson, David E. A. (Communications - Scientific Letters of the University of Zilina, 2015)
This article deals with critical infrastructure and its influence on enterprise economic security. In the introduction, the sectors of critical infrastructure from the point of view of the European Union, Czech Republic and Slovak Republic are characterized. Attention is paid to individual links between the elements of critical infrastructure and the enterprise. Subsequently, enterprise economic security, fundamental factors participating in its creation, and threats disturbing it with emphasis on critical infrastructure failure are discussed. The final part of this article presents possible impacts of critical infrastructure failure on the enterprise economic security.
Keywords: critical infrastructure; enterprise; economic security; threats; failure